The Ointment of Peel Dragon Fruit (Hylicereus costaricensis) Extract Decreased the Interleukin-2 (IL-2) Expression and the Number of Mononuclear Inflammation Cells toward Open Wound in Skin of Rats Wistar - Permata, Fajar Shodiq; Febrianto, Ahmad (Faculty of Veterinary Medicine Universitas Brawijaya, 2019)
Open wounds healing is need more time because of the long inflammatory phase. Dragon fruit skin contains flavonoids and vitamin C which function as anti-inflammatory and cell regeneration. The purpose of this study was to determine the therapeutic effects of dragon fruit skin extract ointment (Hylicereus costaricensis) on the area of IL-2 expression and the number of mononuclear inflammatory cells in skin tissue in open wounds of rats (Rattus norvegicus) for 6 days of treatment. As many as 20 male rats, Â± 180 grams, Wistar were divided into 5 groups namely negative control, positive control, ointment of dragon fruit skin extract with concentration of 5% (P1), concentration of 10% (P2) and concentration of 15% (P3). Wound formed as dorsal skin biopsy of dorsal 1x1 cm. Ointment was given topically 2x/day for 6 days. Rats were euthanized on day 7th and the skin tissues of the wound area were collected. The number of mononuclear inflammatory cells was counted in skin slides of HE staining and Expression Area expression of IL-2 was measured by ImmunoRatioÂ® in immunohistochemical slides. Data were analyzed statistically using One Way ANOVA and Tukey Post Hoc Test. The results showed that dragon fruit skin extract ointment was able to reduce significantly (p<0.05) for area expression of IL-2 and the number of mononuclear inflammatory cells and the best concentration of ointment for treatment was 15%. This is due to the effect of flavonoids as anti-inflammatory and vitamin C as a trigger for cell regeneration. The conclusion of the study was that ointment of dragon fruit peel able to become a candidate for therapeutic medicine for open wounds.